HUBUNGAN TINGKAT KECUKUPAN GIZI, ASUPAN TEMBAGA, SERAT DAN FITAT DENGAN KADAR SENG SERUM ANAK SEKOLAH DASAR BERTUBUH PENDEK DI KARANGAWEN DEMAK - Santi Rahayu; Hertanto Wahyu Subagio; M. Zen Rahfiludin (Universitas Muhammadiyah Semarang, 2005)
Background : Zinc deficiency cause of some inadequate function of the body such as slowed growth and recuce development children. Many factor affect the absorption and excretion zinc in the body that increase risk of zinc deficiency, likes infection disease, physical condition, dan diet factor. Nutrient and phytate in food influences zinc absorption. Objective.' Purpose of this research is to know relation between nutrient and phytate with zinc serum level.Method .' crosss sectional observasional design with cross sectional method. 1 13 Sampel for research are 1